Catching an Entatic State—A Pair of Copper Complexes1. Issue 1 (7th November 2013) - Hoffmann, Alexander; Binder, Stephan; Jesser, Anton; Haase, Roxana; Flörke, Ulrich; Gnida, Manuel; Salomone Stagni, Marco; Meyer‐Klaucke, Wolfram; Lebsanft, Benjamin; Grünig, Lara Elena; Schneider, Simon; Hashemi, Maryam; et al.
Abstract The structures of two types of guanidine–quinoline copper complexes have been investigated by single‐crystal X‐ray crystallography, K‐edge X‐ray absorption spectroscopy (XAS), resonance Raman and UV/Vis spectroscopy, cyclic voltammetry, and density functional theory (DFT). Independent of the oxidation state, the two structures, which are virtually identical for solids and complexes in solution, resemble each other strongly and are connected by a reversible electron transfer at 0.33 V. By resonant excitation of the two entatic copper complexes, the transition state of the electron transfer is accessible through vibrational modes, which are coupled to metal–ligand charge transfer (MLCT) and ligand–metal charge transfer (LMCT) states.